Tending the nurseries of democracy: Mahanoy Area School District v. B.L. and the future of student speech rights. Issue 1 (2nd January 2022) - Herbeck, Dale A.
ABSTRACT: In Mahanoy Area School District v. B.L . (2021), the Supreme Court held a public school could not discipline a student for posting offensive snaps about her cheer team on social media. In an 8-to-1 decision siding with the student, the Justices reaffirmed Tinker v. Des Moines Independent Community School District (1969), a landmark decision by the Warren Court that extended speech rights to public school students. The majority in Mahanoy was, however, unwilling to "set forth a broad, highly general First Amendment rule stating just what counts as 'off-campus' speech and whether First Amendment standards must give way off-campus to the school's desire to prevent … disruption of learning-related activities." Instead, Justice Breyer offered a narrow opinion confined to the facts of the case that provides little practical guidance to students, school officials, and lower courts dealing with thorny issues related to off-campus speech. Further compounding matters, the "three features of off-campus speech" identified in his majority opinion will likely lead to more restrictions governing what students may say on their own time and using their own equipment.